EPC Minutes 2004-10-14 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda amended and approved. Minutes of 8/22/19 amended and approved. Consent Item: Faculty Eligible for Emeritus Status – Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs. Associated Students Report. Staff Representative Report. From EPC: Discontinuance for Minor in Physical Sciences – First Reading Completed. Resolution Requesting Hiatus of Policy Prohibiting FERP Faculty on RTP Committees – Approved. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Good of the Order.